Opportunistic Nectarivory: An Annual Dry Season Phenomenon Among Birds in Monsoonal Northern Australia - Franklin, Donald C. (Emu, 1999)
In the Top End of the Northern Territory, 21 bird species other than honeyeaters, lorikeets and white-eyes were observed to probe flowers in apparent opportunistic nectarivory. Thirteen families were represented. The most frequent opportunists were insectivores, frugivores and a terrestrial omnivore; granivores were also recorded. A vari-ety of nectar sources were exploited but 85% of records were from Darwin Woollybutt Eucalyptus miniata and Fern-leaved Grevillea Grevillea pteridifolia . Opportunistic nectarivory was concentrated particularly in the cool dry season, which in monsoonal Australia is a time of abundant nectar but shortages of fruit and insects. Darwin Woollybutt, Fern-leaved Grevillea and perhaps also the Bloodwood Corymbia opaca may be vital resources upon which a range of species in addition to lorikeets and honeyeaters depend for survival. Emu 99(2) 135 - 141 Full text doi:10.1071/MU99016 © CSIRO 1999